Problems, policy and politics - perspectives of public health leaders on food insecurity and human rights in Australia - Stephanie L. Godrich; Liza Barbour; Rebecca Lindberg (BMC, 2021)
Abstract Background To achieve zero hunger targets set within the United Nations' Agenda 2030, high-income countries such as Australia must reconsider current efforts to improve food security. This study aimed to; explore perspectives from public health nutrition experts on the usefulness of drawing on the international human right to food, and associated mechanisms, to address food insecurity; identify potential roles of key stakeholders in Australia to implement a rights-based approach; and examine barriers and enablers to achieving the right to food in Australia. Methods Qualitative in-depth interviews were conducted with key informants (> 10 years professional experience). Braun and Clarke's (2006) six-phase approach to thematic analysis was employed to analyse data, using Kingdon's multiple streams framework (1984) to examine interactive variables which affect policy-making processes. Results Thirty interviews took place, with most participants representing academia (n = 16), majority had 10-14 years of experience (n = 12) and almost one quarter (n = 7) were in senior leadership roles. Participants believed that framing food insecurity as a human rights issue could be effective when communicating with some audiences, however alternative rhetoric is more popular and potentially more effective. Citizens, government, food industry, non-profit sector, research/tertiary and legal institutions were described as playing critical roles. Barriers to progress were identified as lack of awareness and acknowledgement of the problem, prioritisation of the private sector, lack of political will and domestic laws, and an inefficient/ineffective charitable food sector. Participants identified various enablers and opportunities for implementing a rights-based approach such as grass-roots advocacy efforts to raise awareness of the issue, integrating human rights into government frameworks and community projects and the political will to support action aligned with sustainable development. Conclusions Human rights language and mechanisms have the potential to trigger genuine commitment to addressing food insecurity however should be used with caution. Australia's public health workforce requires increased capacity to implement a human-rights approach and framing such efforts to align with sustainable development may achieve greater political action. Trial registration Ethics approval was received from the Deakin University Human Research Ethics committee (project ID HEAG 168_2018).